Immediate effect of assisted and resisted training using different weight balls on ball speed and accuracy in baseball pitching - Morimoto, Y.; Ito, K.; Kawamura, T.; Muraki, Y. (International Journal of Sport & Health Science, 2003)
The purpose of this study was to investigate the immediate effects of assisted and resisted training using different weight balls on ball speed and accuracy in baseball pitching. Eight male university baseball players assigned as the subjects. Based on the standard ball (145g), two kinds of balls whose weight was increased (weighted ball) or decreased (lightened ball) by 10% were created for the experiment. The subjects were required to pitch these balls and/or standard ball six and eighteen times under the different conditions (training trial): 1) pitched weighted ball only, 2) pitched lightened ball only, 3) pitched standard ball only, and 4) pitched three kinds of balls in order of weighted, standard and lightened ball. Immediate after each training trial, the standard ball was pitched five times respectively (test trial). The ball speed of each trial was measured with a speed gun, and the distance from the center of target to the position of the ball pitched on the target was calculated using a video digitizing system. The results are summarized as follows: 1) In the training trials, the ball speed increased as the ball weight was decreased. 2) In the test trials, immediate after the pitching lightened ball six (6Atest) and eighteen times (18Atest), and three kinds of balls eighteen times (18Ctest), the ball speeds were significantly higher than that of other test trials (p<0.01). 3) Although there were no significant differences in the ball speed among the above three test trials, relatively higher ball speed was observed in 18Atest. 4) As for the distance from the center of target to the position of the ball pitched on the target, there were no significant differences among any trials.